Al-ag-cu alloy film
Patent Information
- Application Number
- TW114109289
- Authority / Receiving Office
- TW · TW
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2026-09-16
- Estimated Expiration
- 2045-03-12
AI Technical Summary
Current charging gun technologies face high energy loss, contact resistance, and wear issues due to the use of precious metals, which are expensive and prone to oxidation, leading to potential fires during high-power charging.
Development of an Al-Ag-Cu alloy thin film with a composite structure of crystalline and amorphous layers, providing high conductivity, wear resistance, and corrosion resistance, fabricated through co-sputtering of Al-Cu and Ag targets.
The Al-Ag-Cu alloy thin film significantly reduces resistance and contact loss, enhances conductivity, and improves mechanical properties, making it suitable for charging gun electrodes and connectors, while being cost-effective.
Smart Images

Figure TWG2TA001075901_001 
Figure TWG2TA001075901_002 
Figure TWG2TA001075901_003
Abstract
Description
Technical Field
[0001] This invention relates to an alloy thin film with high conductivity, wear resistance and corrosion resistance. Specifically, it is an Al-Ag-Cu alloy thin film that can form a combination alloy thin film of crystalline and amorphous layers, and can be applied to charging gun electrodes and conductive connectors. Prior Technology
[0002] With technological advancements, the application scope of charging guns is constantly expanding. Besides electric vehicles, charging guns can also be used in the following types of devices: electric motorcycles and bicycles, electric buses and commercial vehicles, energy storage devices, drones, electric scooters, and other transportation vehicles.
[0003] According to statistics, the energy loss during the charging process of electric vehicles is currently between 10% and 20%, and the degree of energy loss is affected by the charging method.
[0004] AC charging relies on in-vehicle charging equipment (such as an onboard charger) to convert AC power into DC power to charge the battery. The key to the charging process lies in the design of the charger and the coordinated operation of the battery management system to achieve faster charging speeds and higher efficiency.
[0005] DC charging typically uses high-power charging stations to directly deliver high-voltage DC power to the vehicle battery without requiring conversion by an onboard charger. Therefore, the current intensity of DC charging is usually much higher than that of AC charging, making the resistance and conductivity of the conductors more crucial. A charging gun with higher conductivity can improve the efficiency of DC charging.
[0006] For DC charging, it is necessary to improve its resistance loss and contact loss. Resistance loss refers to the loss caused by heat generated by resistance when current passes through wires and connectors. This heat loss is proportional to the square of the current, i.e., P = I²R.
[0007] Contact loss commonly occurs when metal contact surfaces are exposed to air or humid environments. Over time, an oxide or corrosion layer forms. These oxides are insulating and increase contact resistance. Increased contact resistance generates more heat when current flows, exacerbating contact surface loss and even affecting conductivity. Current technology uses precious metals such as gold, platinum, palladium, and ruthenium, and their alloys, to coat the contact terminal surface to increase its weather resistance, making it extremely expensive.
[0008] In addition, during the repeated plugging and unplugging of the charging gun, the friction between the charging gun and the charging port will gradually wear down the precious metal film layer. In addition, most precious metals have low hardness and their protective metal film layer has poor wear resistance, which causes the surface of the copper core terminal to be exposed to the environment and oxidize, thereby further increasing the contact resistance.
[0009] Currently, charging guns have very high charging power (up to 200,000 watts) due to the demand for fast charging. If the contact resistance between terminals increases, the contacts may burn and break during high-power charging, which can easily cause fires. Therefore, it is necessary to develop alloy films with high conductivity, wear resistance, and corrosion resistance for application on the copper electrode surface or conductive connectors of charging guns. Summary of the Invention
[0010] Based on the above requirements, this invention provides an Al-Ag-Cu alloy thin film that is readily available, low in cost, and possesses high conductivity, wear resistance, and corrosion resistance. The alloy thin film containing a crystalline structure exhibits superior conductivity compared to pure copper and pure nickel, while the amorphous alloy thin film shows a significant improvement in mechanical properties compared to pure copper and pure nickel films. Furthermore, the Al-Ag-Cu alloy thin film also exhibits significantly better corrosion resistance than pure copper thin films.
[0011] According to one aspect of the present invention, an alloy thin film is provided, comprising 10.0 to 70.0 mol% aluminum, 15.0 to 65.0 mol% silver and 10.0 to 20.0 mol% copper.
[0012] Furthermore, the alloy film of the present invention has a composite structure of crystalline and amorphous materials. The alloy film with the composite structure of crystalline and amorphous materials not only enables the surface of the copper terminal to have the high conductivity and low resistance characteristics of a crystalline film, but also simultaneously possesses the wear resistance and corrosion resistance of an amorphous film.
[0013] The alloy thin film of the present invention is prepared by co-sputtering Al-Cu alloy target (Al xCu y, x:y=1.5~6) and pure Ag target.
[0014] Specifically, the alloy film of the present invention may be composed of Al 70Ag 15Cu 15, Al 65Ag 15Cu 20, Al 52Ag 31Cu 17, Al 46Ag 35Cu 19, Al 37Ag 46Cu 17, Al 28Ag 59Cu 13 or Al 27Ag 63Cu 10.
[0015] Preferably, in the alloy film of the present invention, the aluminum, silver and copper elements account for more than 90% of the total constituent materials.
[0016] According to another aspect of the present invention, a bilayer alloy thin film is provided, wherein the upper layer has an amorphous structure and the lower layer has a composite structure of crystalline and amorphous materials, and each layer contains 10.0~70.0 moles of aluminum, 15.0~65.0 moles of silver and 10.0~20.0 moles of copper.
[0017] In the bilayer alloy thin film of the present invention, each layer is fabricated by co-sputtering Al-Cu alloy target (Al xCu y, x:y=1.5~6) and pure Ag target.
[0018] Specifically, in the bilayer alloy film of the present invention, the upper layer is composed of Al 40~55Ag 30~40Cu 15~20 and the lower layer is composed of Al 60~70Ag 10~20Cu 10~20. Preferably, the upper layer may be composed of Al 52Ag 31Cu 17 and the lower layer may be composed of Al 70Ag 15Cu 15, or the upper layer may be composed of Al 46Ag 35Cu 19 and the lower layer may be composed of Al 65Ag 15Cu 20.
[0019] Preferably, in the double-layer alloy film of the present invention, the aluminum, silver and copper elements account for more than 90% of the total constituent materials.
[0020] The bilayer alloy thin film of this invention achieves high conductivity through the nanocrystalline structure of the lower layer and wear and corrosion resistance through the amorphous structure of the surface layer, thus solving problems such as resistance loss and contact loss in charging guns during charging. The alloy thin film of this invention can provide low-cost amorphous and crystalline multilayer alloy thin films for existing charging guns and can be applied to the surface of copper electrodes, showing great potential for future applications. Simple Explanation of the Diagram
[0021] Figure 1(a) shows the XRD analysis of Al-Ag-Cu monolayer films with amorphous and crystalline composite structures in Examples 1, 2, 6 and 7; Figure 1(b) shows the XRD analysis of Al-Ag-Cu monolayer films with amorphous structures in Examples 3, 4 and 5.
[0022] Figure 2 shows the Tafel diagram of each component in a single-layer thin film.
[0023] Figure 3 shows the XRD analysis of the Al-Ag-Cu bilayer film of Example 9, wherein the upper layer of the bilayer film has an amorphous structure and the lower layer has a composite structure of amorphous and crystalline structures. Implementation
[0024] The specific implementation of the present invention will be described in more detail below with reference to the drawings and embodiments. Those skilled in the art can easily understand the purpose, features, advantages and effects of the present invention from the disclosure of the embodiments and drawings. However, the present invention is not limited to the contents disclosed in these embodiments and drawings.
[0025] <Preparation of Alloy Thin Films>
[0026] The Al-Ag-Cu alloy thin film of the present invention uses an Al-Cu alloy target (Al xCu y, x:y=1.5~6), and then co-sputters aluminum-copper alloy target and pure silver target using a magnetron sputtering process.
[0027] Aluminum and copper were placed into a heated alumina crucible according to the specified order. Next, a vacuum evacuation and gas refill process was performed, using a bladed rotary pump and a Roots pump until the vacuum level was below 100 mTorr. High-purity argon was introduced, and the pressure was refilled to 0.5 atm for internal purification, repeated three times. Finally, the pressure was evacuated to below 35 mTorr, and argon was refilled to 1 atm to protect the melting process. After all elements had melted and no residual lumpy elements were confirmed, the crucible was tilted, and the molten aluminum-copper alloy was poured into a water-cooled copper mold for cooling. This process yielded the aluminum-copper alloy target.
[0028] Next, the magnetron sputtering process is performed. During vacuum treatment, a mechanical pump is used to evacuate the chamber to approximately 2 × 10⁻² Torr, then a cryogenic pump is switched to further evacuate the vacuum to below approximately 3 × 10⁻⁶ Torr. Simultaneously, the previously prepared aluminum-copper alloy and pure silver targets are cleaned for approximately 10 minutes to prevent oxides or impurities from interfering with sputtering. The co-sputtering wattage is pre-adjusted depending on the desired final alloy film composition. DC magnetron target 1 (silver target): 10 W or 15 W. DC magnetron target 2 (aluminum-copper target): 70 W, 100 W or 130 W.
[0029] The power and sputtering time of the magnetron sputtering process vary depending on the equipment. Those familiar with this technique can adjust it according to their own equipment and their requirements for the composition ratio, crystallinity or amorphousness of the final alloy film.
[0030] After adjusting the power, turn on the shutter to begin co-sputtering, using two DC magnetron targets to jointly output a thin metal film onto the glass substrate.
[0031] When preparing a bilayer film, the preparation time for the first layer, the second layer, and subsequent layers must be calculated first. The baffle must be closed at the specified time, the wattage adjusted, and then the baffle opened to continue preparing the second layer and subsequent layers.
[0032] In the formed alloy film, each layer contains 10.0 to 70.0 mol% aluminum, 15.0 to 65.0 mol% silver and 10.0 to 20.0 mol% copper, and the above main elements account for more than 90 mol% of the total constituent materials.
[0033] After sputtering aluminum-copper alloy and pure silver onto a glass substrate to obtain alloy thin films, their conductivity, mechanical properties and corrosion resistance were tested respectively.
[0034] <Crystal Structure Analysis>
[0035] Examples 1-7 are seven alloy films obtained according to the present invention, which are sorted from high to low according to the content of aluminum element. The specific composition of each alloy film is shown in Table 1 below.
[0036] For the sputtered alloy thin film samples, a low-grazing-angle X-ray diffractometer was first used for analysis to confirm the structure of the metal thin films under different composition ratios, and to understand the crystallinity and amorphousness of the films. Figure 1(a) shows the XRD analysis of Al-Ag-Cu monolayer films with amorphous and crystalline composite structures in Examples 1, 2, 6 and 7, and Figure 1(b) shows the XRD analysis of Al-Ag-Cu monolayer films with amorphous structures in Examples 3, 4 and 5. As can be seen from Figures 1(a) and 1(b), when the contents of aluminum and silver in the film are close, the film structure is more likely to remain in the amorphous (A) state.
[0037] Table 1. Structure and composition of various alloy thin films Example structure composition 1 A+C Al 70Ag 15Cu 15 2 A+C Al 65Ag 15Cu 20 3 A Al 52Ag 31Cu 17 4 A Al 46Ag 35Cu 19 5 A Al 37Ag 46Cu 17 6 A+C Al 28Ag 59Cu 13 7 A+C Al 27Ag 63Cu 10 pure copper C Cu pure nickel C Ni
[0038] <Conductivity Analysis>
[0039] As shown in Table 2 below, in the conductivity analysis of thin films, films containing crystalline structures exhibit superior conductivity compared to pure copper and pure nickel. According to Figure 1(a), Examples 1, 2, 6, and 7 have composite structures of crystalline and amorphous materials, with resistivities of 74.0 μΩ·cm, 49.8 μΩ·cm, 20.6 μΩ·cm, and 15.3 μΩ·cm, respectively, significantly lower than the 42.21 μΩ·cm of pure copper and the 141.13 μΩ·cm of pure nickel. In particular, the resistivity of Example 7 is only 15.3 μΩ·cm, indicating that partially crystalline alloy films exhibit better conductivity and can effectively improve the performance of electronic components.
[0040] The silver content has a significant impact on the conductivity of the alloy. Taking the crystalline alloy film (A+C) as an example, the resistivity decreases significantly with increasing silver content. For instance, the resistivity of Example 7 is 15.3 μΩ·cm, while that of Example 1 is 74.0 μΩ·cm, demonstrating that the addition of silver significantly improves the conductivity of the film. The high conductivity of silver helps reduce the overall resistance of the alloy and promotes the free movement of electrons, thereby improving conductivity efficiency.
[0041] Table 2 Conductivity of various alloy thin films Example structure Conductivity (μΩ·cm) 1 A+C 74.0 2 A+C 49.8 3 A 198.63 4 A 170.85 5 A 34.7 6 A+C 20.6 7 A+C 15.3 pure copper C 42.21 pure nickel C 141.13
[0042] <Mechanical Properties>
[0043] The results of the mechanical property measurements are shown in Table 3 below. The amorphous alloy films exhibit significant improvements in mechanical properties compared to pure copper and pure nickel films. The alloy films generally have higher hardness; for example, the hardness of Example 3 is 4.88 GPa, significantly higher than the 2.35 GPa of pure copper, indicating that the alloy possesses better compressive strength and wear resistance. Furthermore, the alloy's Young's modulus shows better rigidity; the Young's modulus of Example 5 reaches 78.29 GPa, significantly higher than the 68.84 GPa of pure copper, meaning that the alloy deforms less under stress and can better maintain its shape.
[0044] Among these components, the H3 / E2 value is used to measure the material's resistance to plastic deformation; a higher value indicates that the material is less prone to deformation. It can be seen that although the Al-Ag-Cu alloy film contains a significant proportion of silver, its completely amorphous (A) or partially amorphous (Amorphous+Crystalline, A+C) structure results in a high H3 / E2 value, meaning it has good resistance to plastic deformation. Conversely, crystalline (C) films (such as pure Cu and Ni) have lower H3 / E2 values, indicating weaker resistance to plastic deformation. Overall, amorphous materials exhibit better resistance to plastic deformation than crystalline materials.
[0045] Table 3 Mechanical properties of various alloy thin films Example structure hardness (GPa) Young's modulus (GPa) H3 / E2 1 A+C 2.52±0.47 76.43±8.10 0.0030 2 A+C 3.32±0.56 90.79±6.26 0.0040 3 A 4.88±0.22 100.71±4.03 0.0180 4 A 4.47±0.32 80.81±3.00 0.0090 5 A 6.83±0.06 78.29±0.69 0.0520 6 A+C 6.66±0.13 75.90±0.24 0.0510 7 A+C 6.28±0.06 72.60±0.01 0.0470 pure copper C 2.35±0.34 68.84±5.76 0.0027 Sterling silver C 5.28±0.37 128.90±4.44 0.0088
[0046] <Corrosion resistance>
[0047] In terms of corrosion resistance, Al-Ag-Cu alloy films show a significant advantage over pure copper films. Firstly, regarding the corrosion potential (corrosion voltage), as shown in Table 4, the corrosion potential of the amorphous film is higher than that of pure copper (-0.182 V). For example, the corrosion potential of Example 3 is -0.07 V, while that of Example 4 is -0.162 V. This indicates that the amorphous film has higher stability in corrosive environments and better corrosion resistance.
[0048] Secondly, in terms of current density, the Al-Ag-Cu alloy film exhibits a relatively low current density. Taking Example 3 as an example, its current density is 10⁻⁵.56 A, indicating a low rate of metal ion dissolution during corrosion, meaning a slower corrosion rate. In contrast, pure copper has a current density of 10⁻³.53 A, showing a higher corrosion rate under the same conditions.
[0049] Table 4 Corrosion potential and current density of various alloy films Example structure Corrosion potential (V) Current density (A) 1 A+C -0.53 10 -3.28 2 A+C -0.304 10 -3.48 3 A -0.07 10 -5.56 4 A -0.162 10 -3.37 pure copper C -0.182 10 -3.53
[0050] <Double-layer alloy thin film>
[0051] Combining the characteristics of crystalline and amorphous thin films described above, this invention further develops a bilayer thin film possessing high conductivity, wear resistance, and corrosion resistance. By combining amorphous and crystalline structures, the bilayer alloy thin film of this invention achieves a resistivity of less than 40 μΩ·cm when the silver content is less than 50%.
[0052] In terms of structural design, the crystalline structure is deposited on the lower layer (thickness 800 nm), while the amorphous structure is deposited on the upper layer (thickness 200 nm). In Example 8, the upper layer is Al 52Ag 31Cu 17(A), and the lower layer is Al 70Ag 15Cu 15(A+C), equivalent to a combination of Example 3 and Example 1. In Example 9, the upper layer is Al 46Ag 35Cu 19(A), and the lower layer is Al 65Ag 15Cu 20(A+C), equivalent to a combination of Example 4 and Example 2. Referring to Figure 3, the XRD results show that the peak value of Example 9 exhibits both amorphous and crystalline characteristic peaks of Examples 4 and 2. The conductivity test results show that the resistivity of the two bilayer films in Examples 8 and 9 are 30.8 μΩ·cm and 47.01 μΩ·cm, respectively, significantly lower than that of pure copper (42.21 μΩ·cm) and pure nickel (141.13 μΩ·cm).
[0053] Furthermore, the nano-indentation test results showed that the hardness of Example 8 was 6.65 GPa, while that of Example 9 was 6.58 GPa, both of which were much higher than the 2.35 GPa of pure copper.
[0054] In summary, the bilayer alloy film of this invention not only exhibits excellent electrical conductivity but also significant hardness, demonstrating its potential in demanding applications.
[0055] Table 5. Electrical conductivity and mechanical properties of bilayer alloy thin films Example conductivity (μΩ·cm) hardness (GPa) Young's modulus (GPa) H3 / E2 8 30.80 6.65±0.34 69.49±4.01 0.0609 9 47.01 6.58±0.21 70.10±3.69 0.0579 pure copper 42.21±1.38 2.35±0.34 68.84±5.76 0.0027 pure nickel 141.13±2.00 5.28±0.37 128.90±4.44 0.0088
[0056] In summary, the alloy thin film exhibits superior conductivity compared to pure copper and pure nickel films, making it more promising for subsequent electrical applications. In particular, the increased silver content further improves the alloy's conductivity, demonstrating the significant impact of alloy composition tempering on material conductivity. Furthermore, the amorphous Al-Ag-Cu alloy thin film demonstrates superior wear resistance and corrosion resistance compared to pure copper, making it a highly attractive choice for subsequent conductive material applications, especially for copper electrodes in charging guns where improved corrosion and wear resistance are required. These data support the potential of alloy thin films to reduce resistance and contact losses, particularly in electronic and mechanical applications.
[0057] The present invention has been described with reference to the specific embodiments described above; however, these embodiments are merely illustrative and not intended to limit the invention. Various modifications and variations can be made to the invention by those skilled in the art without departing from the spirit and scope of the invention as defined in the appended claims, for example, but not limited to, further co-sputtering to form three or more alloy thin films. The present invention is intended to include such modifications and variations.
Claims
1. An alloy thin film comprising 10.0 to 70.0 mol% aluminum, 15.0 to 65.0 mol% silver and 10.0 to 20.0 mol% copper.
2. The alloy thin film as claimed in claim 1, wherein, The alloy film has a composite structure of crystalline and amorphous materials.
3. The alloy thin film as requested in item 1 or 2, wherein, The alloy thin film was prepared by co-sputtering Al xCu y (x:y=1.5~6) alloy target with pure Ag target.
4. The alloy thin film as requested in item 1 or 2, wherein, The alloy film has the following composition: Al 70Ag 15Cu 15, Al 65Ag 15Cu 20, Al 52Ag 31Cu 17, Al 46Ag 35Cu 19, Al 37Ag 46Cu 17, Al 28Ag 59Cu 13, or Al 27Ag 63Cu 10.
5. The alloy thin film as requested in item 1 or 2, wherein, These aluminum, silver, and copper elements account for more than 90% of the total composition of the materials.
6. A bilayer alloy thin film, characterized in that: the upper layer has an amorphous structure, and the lower layer has a composite structure of crystalline and amorphous materials, wherein, Each layer contains 10.0 to 70.0 mol% aluminum, 15.0 to 65.0 mol% silver, and 10.0 to 20.0 mol% copper.
7. The double-layer alloy film as claimed in claim 6, wherein, Each layer was fabricated by co-sputtering Al xCu y (x:y=1.5~6) alloy target and pure Ag target.
8. The double-layer alloy film as claimed in item 6 or 7, wherein, The upper layer consists of Al 40~55, Ag 30~40, and Cu 15~20, while the lower layer consists of Al 60~70, Ag 10~20, and Cu 10~20.
9. The double-layer alloy thin film as claimed in claim 8, wherein, The upper alloy film has the composition of Al 52Ag 31Cu 17 and the lower alloy film has the composition of Al 70Ag 15Cu 15.
10. The double-layer alloy thin film as claimed in claim 8, wherein, The upper alloy film has the composition of Al 46Ag 35Cu 19 and the lower alloy film has the composition of Al 65Ag 15Cu 20.
11. The double-layer alloy film as claimed in item 6 or 7, wherein, These aluminum, silver, and copper elements account for more than 90% of the total composition of the materials.
